2020
DOI: 10.1002/sia.6827
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation to discover rheological properties and soil‐binding ability of PHPA polymer on montmorillonite surface

Abstract: Synthetic polymer fluids are increasingly being applied to support excavations in deep foundations. As these fluids are molecularly engineered, their underlying microstructure interaction with in situ soils significantly affect excavation stability and soil dispersion. However, little molecular‐scale research has been done on the rheological behavior of partially hydrolyzed polyacrylamides (PHPA) polymer fluids on the clay surface. Molecular models of the clay–polymer systems are constructed using PHPA on mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The bonding associated with the particles in a drilling fluid model affects the thermal stability of the fluid. This study demonstrated that the chemical bonding between the polymer and silica composite is probably van der Waals or electrostatic forces since it is physical mixing between PAM, functionalized SiO 2 , and SDS 5,66‐69 . According to the interfacial chemistry of substances, a composite with electrostatic or van der Waals forces is poorer than a composite developed through covalent bonding 67 .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The bonding associated with the particles in a drilling fluid model affects the thermal stability of the fluid. This study demonstrated that the chemical bonding between the polymer and silica composite is probably van der Waals or electrostatic forces since it is physical mixing between PAM, functionalized SiO 2 , and SDS 5,66‐69 . According to the interfacial chemistry of substances, a composite with electrostatic or van der Waals forces is poorer than a composite developed through covalent bonding 67 .…”
Section: Resultsmentioning
confidence: 85%
“…This study demonstrated that the chemical bonding between the polymer and silica composite is probably van der Waals or electrostatic forces since it is physical mixing between PAM, functionalized SiO 2 , and SDS. 5,[66][67][68][69] According to the interfacial chemistry of substances, a composite with electrostatic or van der Waals forces is poorer than a composite developed through covalent bonding. 67 Additionally, the covalent bonding between the polymer chains and the polymer molecules is present in bare PAM.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, the authors focused on predicting the mechanical, 66–68 rheological, 69,70 or thermodynamical properties 71,72 of the PCNC materials. On the other hand, many other researchers investigated the adsorption mechanisms of polymers and provided insights on how to enhance the adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…62 While most researchers chose montmorillonite (MMT) to represent clay, some other studies considered other types of clay including quartz, 63 kaolinite, 64 and silica. 65 In many studies, the authors focused on predicting the mechanical, 66-68 rheological, 69,70 or thermodynamical properties 71,72 of the PCNC materials. On the other hand, many other researchers investigated the adsorption mechanisms of polymers and provided insights on how to enhance the adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their applications in some micro-scale geotechnical problems have become a research hotspot [24], as these problems occur in frozen, saline, and expansive soils. As the main component of most soils, clay minerals have been widely studied, including the micro-mechanisms of surface wettability [25], matter adsorption [26], mechanical properties [27], and, most importantly, clay swelling [28]. With the advancement of computer power and algorithms [29], they are increasingly used to obtain information on clay swelling, where the interlamellar spacings are smaller than the Debye length (∼20 Å), and the hydration effects become essential [30].…”
Section: Introductionmentioning
confidence: 99%